Growth and adjustment in a petroleum-based economy : some aspects of the Trinidad and Tobago experience since the 1970s. - RAMSARAN, Ramesh F. (1993)
Examines recent growth experience of Trinidad and Tobago, and developments in the external sector. Discusses issues affecting government finance, and explains the relationship between domestic credit and the balance of payments.